Analisis Model Pembelajaran IPAS Di SDN Pangarangan III - Nur aini; Muallimah; Herdi hardiyansah; Khairul umam (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
This study aims to describe and analyze in depth the Natural and Social Sciences (IPAS) learning models at SDN Pangarangan III. Using a qualitative descriptive approach, data were collected through direct observation of the learning process and interviews with classroom teachers regarding model selection, challenges, and results achieved. The results show that SDN Pangarangan III has moved away from one-way interaction patterns and transitioned to innovative models such as Project Based Learning (PjBL) and Discovery Learning. The implementation of PjBL has proven effective in integrating multidimensional IPAS concepts, training problem-solving skills, and developing students' affective and emotional domains through collaboration. Despite challenges such as limited media resources and tight time allocations, teachers have made strategic adjustments to maintain learning effectiveness. This study emphasizes that the analysis and modification of learning models are crucial to ensuring pedagogical practices remain relevant to the independent curriculum (Kurikulum Merdeka) and the unique needs of students.